2019
DOI: 10.1111/jfbc.12968
|View full text |Cite
|
Sign up to set email alerts
|

The antioxidant activity and active sites of delphinidin and petunidin measured by DFT, in vitro chemical‐based and cell‐based assays

Abstract: A computational DFT B3LYP method with 6‐311G (d,p) basis set, the in vitro chemical‐based and cellular antioxidant activity (CAA) assays were applied in this study to explain the structure–antioxidant activity relationships of delphinidin and petunidin. The compound molecular structures, spectral properties, frontier orbital energy, and transition state of delphinidin and petunidin were compared. In transition state, the result of the active site (O21–H32 and O22–H33) was consistent with the result of bond len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 48 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…Pg, Mv, and Pn with only one À OH group in the B-ring had lower activities compared to Cy and Dp with more than one À OH substitution assessed by ORAC, 1,1diphenyl-2-picrylhydrazyl (DPPH), 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assays. [16,101,102] These results demonstrated that the structure 3'-4' catechol was highly determinant in scavenger activity. [95]…”
Section: Hydroxy Groups-hydroxylationmentioning
confidence: 65%
See 1 more Smart Citation
“…Pg, Mv, and Pn with only one À OH group in the B-ring had lower activities compared to Cy and Dp with more than one À OH substitution assessed by ORAC, 1,1diphenyl-2-picrylhydrazyl (DPPH), 2,2'-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) assays. [16,101,102] These results demonstrated that the structure 3'-4' catechol was highly determinant in scavenger activity. [95]…”
Section: Hydroxy Groups-hydroxylationmentioning
confidence: 65%
“…The authors suggested that the hydroxy groups on the 3′ and 4′ positions in the B‐ring were important determinants for the radical scavenging potential in anthocyanins, while the 5′‐hydroxylation appeared to decrease the ORAC activity in the presence of 3′ and 4′‐OH. Pg, Mv, and Pn with only one −OH group in the B‐ring had lower activities compared to Cy and Dp with more than one −OH substitution assessed by ORAC, 1,1‐diphenyl‐2‐picrylhydrazyl (DPPH), 2,2’‐azinobis‐3‐ethylbenzothiazoline‐6‐sulfonic acid (ABTS) assays [16,101,102] . These results demonstrated that the structure 3’‐ 4’ catechol was highly determinant in scavenger activity [95] …”
Section: The Role Of Anthocyanins In the Antioxidative Capacities Of Pomegranatementioning
confidence: 90%
“…Moreover, chronic and acute treatments could affect Nrf2 pathway that was related to cardiovascular risk (Hine & Mitchell, 2012; Kaspar et al., 2009). Petunidin showed strong antioxidant effects in our study (Figure 2 to 3), and we found that the antioxidant activity of petunidin was higher than delphinidin with the cell‐based antioxidant activity determined by CAA (Chen et al., 2019), which is probably because the methoxy groups in the B ring increased the stability of the resulting phenoxy radical (Lapidot, Harel, Akiri, Granit, & Kanner, 1999). In our study, petunidin and lycopene showed protective effects in suppressing H 2 O 2 ‐induced oxidative stress in cardiomyocytes via Akt/Nrf2 pathway (Figure 2 to 7), showing that the compounds have potential effects to reduce cardiovascular risk.…”
Section: Resultsmentioning
confidence: 59%
“…Petunidin (Figure 1A) in its glycosidic forms has been found in purple potatoes (Jiang et al., 2016; Zhang et al., 2017). The antioxidant activity of petunidin was higher than delphinidin with the cell‐based antioxidant activity determined by the cellular antioxidant activity (CAA) (Chen et al., 2019). Also, petunidin glycosides from purple potato were more readily taken up by the Caco‐2 cells in the transmembrane system, which was attributed to a stronger anti‐inflammatory effect in vitro (Zhang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Based on DFT calculations, Chen et al . found that the active sites of delphinidin and petunidin (O21–H32 and O22–H33) may enhance antioxidant activity through transition states 24 . Although flavylium cation, hemiketal, quinoidal base, cis ‐ and trans ‐chalcone species in aqueous solutions, most of the studies focus on the antioxidant activities of flavonoid cations, and there is little information about other structural activities.…”
Section: Introductionmentioning
confidence: 99%